Morphological characteristics of the walls of thrombophlebitic saphenous vein. (April 2014) - Jian, F-G; Chu, H-B; Liu, G-Z; Zhao, J-H; Xu, Y-B; Wang, T; Sun, H-J; Tang, J-Y; Guo, W-J; Wu, H-J; Zhang, S-M
Introduction: To investigate the morphological changes in the walls of thrombophlebitic saphenous veins. Methods: Fifty-four specimens were made into slices for haematoxylin and eosin and Masson trichrome staining; ultrathin slices were also created. Slices were observed under light microscopy and electron microscopy. Results: Under light microscopy, the tunica intima of venous wall in the thrombophlebitic saphenous veins group was obviously thickened and incomplete; intravascular papillary endothelial hyperplasia was observed. Hyperplasia of collagenous fibres in the tunica media was observed. Elastic fibres in the tunica externa became fewer, whereas nourishing vessels were significantly increased in number. Infiltration of many inflammatory cells was observed. Under electron microscopy, Auer bodies with high electron density and round granules could be seen in endothelial cells in the thrombophlebitic saphenous veins group. Smooth muscle cells had an irregular karyotype, with blurred cristae in some mitochondria. Myofilaments basically disappeared. Conclusion: Thrombus formation might aggravate re-modelling of the walls of varicose veins.